Trading activities and the volatility of return on Malaysian crude palm oil futures - Xiu Wei Yeap; Hooi Hooi Lean (Journal of Risk and Financial Management, 2022)
Trading activities represent the flow of market information to the investors. This paper examines the effect of trading activities, i.e., trading volume and open interest, on the volatility of return for Malaysian Crude Palm Oil Futures. The GARCH model is applied by adding the expected and unexpected elements of trading activities (trading volume and open interest) as the independent variables. The results show that there is a negative contemporaneous relationship between the expected volume and volatility, but that a positive relationship exists between unexpected volume and volatility. On the contrary, the expected and unexpected open interest mitigate the volatility. Therefore, both trading volume and open interest should be considered together when information flows into the market.
Keywords: G14; Q10; 330; crude palm oil futures; trading volume; open interest; market information